N‐Substituted piperidine‐3‐carbohydrazide‐hydrazones against Alzheimer's disease: Synthesis and evaluation of cholinesterase, beta‐amyloid inhibitory activity, and antioxidant capacity. Issue 3 (3rd December 2022) - Parlar, Sulunay; Sayar, Gozde; Tarikogullari, Ayse H.; Karadagli, Sumru Sozer; Alan, Elif; Sevin, Gulnur; Erciyas, Ercin; Holzgrabe, Ulrike; Alptuzun, Vildan
Abstract: A series of piperidine‐3‐carbohydrazide‐hydrazones bearing phenylethyl, phenylpropyl, and phenylbutyl substituents on piperidine nitrogen were designed and synthesized as cholinesterase (ChE) inhibitors. The title compounds were screened for acetylcholinesterase (AChE), butyrylcholinesterase (BuChE) inhibitory activities and antioxidant capacities, and the active ones for Aβ42 self‐aggregation inhibition, in vitro. The chemiluminescence method was used to determine the effect of the selected compounds on the reactive oxygen species (ROS) levels in brain tissue. Physicochemical properties were calculated by the MOE program. Kinetic analysis and molecular modeling studies were also carried out for the most active compounds. Generally, the final compounds exhibited moderate to good AChE or BuChE inhibitory activity. Among them, 3g and 3j showed the most potent activity against AChE (IC50  = 4.32 µM) and BuChE (IC50  = 1.27 µM), respectively. The kinetic results showed that both compounds exhibited mixed‐type inhibition. Among the selected compounds, nitro derivatives (3g, 4g, and 5g ) provided better Aβ42 inhibition. According to the chemiluminescence assay, 4i exhibited the most active superoxide free‐radical scavenger activity and 3g, 3j, and 4i showed similar scavenger activity on other ROS. All results suggested that 3g, 3j, and 4i have good AChE/BuChE, Aβ42 inhibitory potentials and antioxidant capacities and can therefore be suggested as promising multifunctional agents to combat Alzheimer's disease. Abstract : A series of piperidine‐3‐carbohydrazide‐hydrazones bearing phenylethyl, phenylpropyl, and phenylbutyl substituents on piperidine nitrogen were designed and synthesized as acetyl‐/butyrylcholinesterase (AChE/BuChE) inhibitors. Compounds 3g, 3j, and 4i have good AChE/BuChE and Aβ42 inhibitory potentials and antioxidant capacities and can therefore be suggested as promising multifunctional agents to combat Alzheimer's disease.